Assessment of the livestock-feed and water nexus across a mixed crop-livestock system’s intensification gradient: An example from the Indo-Ganga basin - Haileslassie, Amare; Blümmel, Michael; Clement, Floriane; Descheemaeker, Katrien K.; Amede, Tilahun; Samireddypalle, A.; Acharya, Sreedhar; Radha, A.Venkata; Ishaq, S.; Samad, M.; Murty, M.V.R.; Khan, M.A. (Cambridge University Press, 2011)
Projections suggest that annual per capita water availability in the Indo-Ganga Basin (IGB) will reduce to a level typical for water-stressed areas. Producing more crop and livestock products, per unit of agricultural water invested, is advocated as a key strategy for future food production and environmental security in the basin. The objective of this study was to understand the spatio-temporal dynamics of water requirements for livestock feed production, attendant livestock water productivity (LWP) and implications for the future sustainable use of water resources. We focused on three districts in the IGB representing intensive (higher external inputs, e.g. fertilizer, water) and semi-intensive (limited external input) crop-livestock systems. LWP is estimated based on principles of water accounting and is defined as the ratio of livestock beneficial outputs and services to the water depleted and degraded in producing these. In calculating LWP and crop water productivity (CWP), livestock, land use, land productivity and climatic data were required. We used secondary data sources from the study districts, field observations and discussions with key informants to generate those data sets. Our result showed that the volume of water depleted for livestock feed production varied among the study systems and was highly affected by the type of feed and the attendant agronomic factors (e.g. cropping pattern, yield). LWP value was higher for intensive systems and affected by agricultural water partitioning approaches (harvest index, metaolizable energy). LWP tended to decrease between 1992 and 2003. This can be accounted for by the shift to a feeding regime that depletes more water despite its positive impacts on animal productivity. This is a challenging trend with the advent of and advocacy for producing more agricultural products using the same or lower volume of water input and evokes a need for balanced feeding, by considering the nutritive value, costs and water productivity of feed, and better livestock management to improve LWP.